2014
DOI: 10.1016/j.neulet.2014.01.056
|View full text |Cite
|
Sign up to set email alerts
|

Estimating brain network activity through back-projection of ICA components to GLM maps

Abstract: Independent component analysis (ICA) is a data-driven approach frequently used in neuroimaging to model functional brain networks. Despite ICA’s increasing popularity, methods for replicating published ICA components across independent datasets have been underemphasized. Traditionally, the task-dependent activation of a component is evaluated by first back-projecting the component to a functional MRI (fMRI) dataset, then performing general linear modeling (GLM) on the resulting timecourse. We propose the alter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…This process was repeated for all participants, components, and task fMRI datasets. Figure S1 illustrates this process, which is validated and fully described elsewhere (James et al 2014).…”
Section: Extracting Component Activity Timecoursesmentioning
confidence: 92%
“…This process was repeated for all participants, components, and task fMRI datasets. Figure S1 illustrates this process, which is validated and fully described elsewhere (James et al 2014).…”
Section: Extracting Component Activity Timecoursesmentioning
confidence: 92%
“…The relationship of each component to intertemporal reward decision-making was tested by regressing component maps on each subject’s WANT>CON contrast maps (Fig. 1C) as an alternative to estimating this relationship with GLM analyses of component time series (James, Tripathi, & Kilts, 2014). The resulting contrast estimates were mean and variance normalized by converting them to z -scores.…”
Section: Methodsmentioning
confidence: 99%
“…Final component number was determined using the stability index (Iq), which reflect the internal stability of a component. K = 15 components was the smallest k value to meet a high Iq threshold (mean Iq, .0.95; minimum Iq, .0.90; Himberg et al, 2004;Turner et al, 2012;James et al, 2014). Qualitative follow-up examination revealed that adjacent component amounts (e.g., k = 14 and k = 16) resulted in nearly identical findings, while examinations of (1) low total components (e.g., k = 4) showed a merging of significant subcomponents (e.g., the P600 was a single component, whereas higher component amounts subdivided the P600 into subcomponents that significantly contributed to the raw data); and (2) high total components (e.g., k = 21) showed a division of relevant subcomponents so that they did not meet contribution thresholds.…”
Section: Experimental Design and Statistical Analysismentioning
confidence: 99%